Risk factors for hyperglycemia in pregnancy in the DALI study differ by period of pregnancy and OGTT time point. Issue 1 (July 2018) - Mendoza, Lilian C; Harreiter, Jürgen; Simmons, David; Desoye, Gernot; Adelantado, J M; Juarez, Fabiola; Chico, Ana; Devlieger, Roland; van Assche, Andre; Galjaard, Sander; Damm, Peter; Mathiesen, Elisabeth R; et al.
Abstract : Objective: Risk factors are widely used to identify women at risk for gestational diabetes mellitus (GDM) without clear distinction by pregnancy period or oral glucose tolerance test (OGTT) time points. We aimed to assess the clinical risk factors for Hyperglycemia in pregnancy (HiP) differentiating by these two aspects. Design and methods: Nine hundred seventy-one overweight/obese pregnant women, enrolled in the DALI study for preventing GDM. OGTTs were performed at ≤19 + 6, 24–28 and 35–37 weeks (IADPSG/WHO2013 criteria). Women with GDM or overt diabetes at one time point did not proceed to further OGTTs. Potential independent variables included baseline maternal and current pregnancy characteristics. Statistical analysis: Multivariate logistic regression. Results: Clinical characteristics independently associated with GDM/overt diabetes were at ≤19 + 6 weeks, previous abnormal glucose tolerance (odds ratio (OR): 3.11; 95% CI: 1.41–6.85), previous GDM (OR: 2.22; 95% CI: 1.20–4.11), neck circumference (NC) (OR: 1.58; 95% CI: 1.06–2.36 for the upper tertile), resting heart rate (RHR, OR: 1.99; 95% CI: 1.31–3.00 for the upper tertile) and recruitment site; at 24–28 weeks, previous stillbirth (OR: 2.92; 95% CI: 1.18-7.22), RHR (OR: 3.32; 95% CI: 1.70-6.49 for the upper tertile) and recruitment site; at 35–37 weeks, maternal height (OR: 0.41; 95% CI: 0.20–0.87 for upper tertile). Clinical characteristics independently associated with GDM/overt diabetes differed by OGTT time point (e.g. at ≤19 + 6 weeks, NC was associated with abnormal fasting but not postchallenge glucose). Conclusion: In this population, most clinical characteristics associated with GDM/overt diabetes were non-modifiable and differed by pregnancy period and OGTT time point. The identified risk factors can help define the target population for future intervention trials.